2020
DOI: 10.1111/jcmm.16230
|View full text |Cite
|
Sign up to set email alerts
|

Role of gut microbiota‐derived metabolites on vascular calcification in CKD

Abstract: The interaction between gut microbiota and the host has gained widespread concern. Gut microbiota not only provides nutrients from the ingested food but also generates bioactive metabolites and signalling molecules to impact host physiology, especially in chronic kidney disease (CKD). The development of CKD, accompanied by changed diet and medication, alters the gut flora and causes the effect in distant organs, leading to clinical complications. Vascular calcification (VC) is an actively regulated process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 99 publications
0
28
0
Order By: Relevance
“… 74 This disproportionate amount of plasmatic uremic toxins prompts the production of free radicals in both renal cells and VSMC through oxidative stress and inflammation, causing tissue injury. 75 IS induces the expression of osteoblast‐specific proteins and aortic wall calcification and thickening in Dahl salt‐sensitive hypertensive rats. 76 In line, IS has been shown to promote a phenotypic switch of vascular smooth muscular cells (VSMC) from a contractile to an osteogenic phenotype.…”
Section: Gut‐vascular‐bone Axis In Ckdmentioning
confidence: 99%
See 1 more Smart Citation
“… 74 This disproportionate amount of plasmatic uremic toxins prompts the production of free radicals in both renal cells and VSMC through oxidative stress and inflammation, causing tissue injury. 75 IS induces the expression of osteoblast‐specific proteins and aortic wall calcification and thickening in Dahl salt‐sensitive hypertensive rats. 76 In line, IS has been shown to promote a phenotypic switch of vascular smooth muscular cells (VSMC) from a contractile to an osteogenic phenotype.…”
Section: Gut‐vascular‐bone Axis In Ckdmentioning
confidence: 99%
“… 127 SCFA seems to contribute to the improvement of vascular phenotypes. 75 Some studies have shown immunomodulatory capacities of SCFA. Inflammatory cells such as neutrophils, macrophages, dendritic cells and T cells are responsive to SCFA treatment, in line with their anti‐inflammatory effects in a wide range of inflammatory diseases, and reduction of vascular calcification, 128 although studies in this field are still limited.…”
Section: Gut‐vascular‐bone Axis In Ckdmentioning
confidence: 99%
“…Serum TMAO concentrations in animals fed with experimental diets: 7.0 µmol/L (fish), 1.0 µmol/L (casein) and 1.5 µmol/L (soy) More advanced atherosclerosis and more calcified atherosclerotic lesions in animals fed with fish protein Aortic wall mRNA expression of of several inflammatory markers (including CD36, IL6 and ICAM-1) significantly higher in animals fed with fish protein Clinical trial [85] Observational trial of 817 apparently healthy participants aged between 33 No association between baseline serum TMAO and any of the analyzed outcomes, including: Cardiac death, sudden cardiac death, first CV event, death from any cause for the whole group and among Black patients TMAO significantly associated with all above endpoints among Whites The difference in outcome between races despite comparable serum TMAO between respective groups 1 IS, pCS and TMAO concentrations in experiments comparable to average serum concentrations in uremic patients.…”
Section: Model Design and Methods Key Findingsmentioning
confidence: 99%
“…The most important substances identified to impact on the endothelial cells and VSMC, and to promote VC include: Advanced glycation end-products, PCS, IS and trimethylamine-N-oxide (TMAO); Pi and phosphaturic hormones (such as parathyroid hormone and phosphatonin FGF23 are also classified by some authors as uremic toxins) [29][30][31]. Since gut microbiota is the most important source of PCS, IS and TMAO, uremia-dependent or kidney disease-specific gut microbiota abnormalities (dysbiosis) may also contribute to VC [32,33].…”
Section: Selected Mechanisms Of Vc Regulationmentioning
confidence: 99%
“…By comparing the microbial community structures between lung and intestine bacteria, evidence reveals that members of lung and intestine bacteria can directly exchange through the lymph circulation [ 51 , 52 , 53 ]. Additionally, gut microbiota can produce various kinds of bioactive metabolites (such as butyrate, p-cresol sulfate, and indoles) to impact the host immune response and energy homeostasis [ 54 , 55 , 56 , 57 , 58 ]. The innate lymphoid cells (ILCs) derived from intestinal lamina propria have important action on host defense and inflammatory responses.…”
Section: Relations Between the Gut Microbiota And Lung Microbiota Med...mentioning
confidence: 99%